Green synthesis of bioactive polysaccharide-capped gold nanoparticles for lymph node CT imaging. (1st February 2018) - Uthaman, Saji; Kim, Hyeon Sik; Revuri, Vishnu; Min, Jung-Joon; Lee, Yong-kyu; Huh, Kang Moo; Park, In-Kyu
Graphical abstract: Highlights: M-GNPs as CT contrast agent for lymph node imaging. M-GNPs were spherical nanoparticles with an average diameter of 9.18 ± 0.71 nm. M-GNPs exhibited mannose receptor mediated endocytosis in antigen presenting cells. Local administration of M-GNPs led to significantly enhanced X-ray imaging of popliteal lymph nodes. Abstract: The development of biologically targeted contrast agents for X-ray computed tomography (CT) imaging remains a major challenge. Here, we investigated a green chemistry-based synthesis of lymph node-targeted mannan-capped gold nanoparticles (M-GNPs) as a CT contrast agent. In this study, mannan was used as a reducing and stabilizing agent for gold nanoparticles (AuNPs). M-GNPs were readily internalized by antigen-presenting cells (APCs) through mannose receptors-mediated endocytosis. The M-GNPs, which had a spherical morphology, had an average diameter of 9.18 ± 0.71 nm and surface plasmon resonance (SPR) absorption spectra with maximal absorption at 522 nm. The M-GNPs displayed a concentration-based X-ray attenuation property with a maximum Hounsfield unit (HU) value of 303.2 ± 10.83. The local administration of M-GNPs led to significantly enhanced X-ray contrast for the imaging of popliteal lymph nodes. These findings demonstrated that M-GNPs can be used as biologically targeted contrast agents for CT imaging.